FREQUENCY ANALYSIS OF TWO-YEARS OBSERVATIONS OF RR LYRAE - Yushchenko, A. V.; Romanov, Yu. S.; Lemeshchenko, N. D.; Murnikova, V. P. (Одеські астрономічні публікації, 2017)
2964 photoelectric observation of RR Lyrae were obtained at the Odessa observatory during two years: 1977 and 1978. Observations were transformed to standard BV photometric system and frequency-analyzed in the interval 0.08-700 days. A number of harmonics were detected. The main harmonic coincides with the well known photometric period (v0=1.764129), second harmonic ( vb=1.789093) is related with a period of Blazhko effect. There is a sequence of harmonics, which can be written by equation v=kv0 + vb where k=0,1,2,3,4. Two harmonics are connected with known periods of RR Lyrae: 123 days and four years.